KÜTÜPHANELERDE BİLGİSAYAR KULLANIMININ GETİRDİĞİ SORUNLAR - Nilüfer Tuncer (Türk Kütüphaneciliği)
Recently in Turkey, there is a tendency toward using computer in library work without really considering its disadvantages or limitations. Computer-based problems are reloted with hardware, telecommunications, personnel, user, budget, administration and buildings, vollection and evaluation. Despite limitations, however, computer use especially for literature searches, is advised if librarians want to stay in the profession.